NUMERICAL ANALYSIS OF THE BEHAVIOUR OF A LARGEDIAMETER MONOPILE FOR OFFSHORE WIND TURBINES - Ahlinhan, Marx Ferdinand; ADJOVI, EDMOND CODJO; DOKO, KOUANDETÉ VALERY; TIGRI, Tertulie Lamatou Nawal (My University, 2019)
Very-large-diameter monopiles are widely used foundations for offshore wind turbines, despite the limited guidance in the codes of practice. In the present study, three-dimensional finite-element (FE) analyses were carried out to determine the static capacity of a monopile embedded in sand subjected to combined loading. A hardening soil model (HSM) accounting for the stress dependence of the soil stiffness was used for the numerical model, which was calibrated with the results of published centrifuge tests. Based on a parametric study for different length-to-diameter ratios of the monopile, lateral load-moment interaction diagrams for the ultimate limit state as well as for the serviceability limit state were developed for different relative densities of the foundation sand. Furthermore, the initial stiffness formulations for the monopile system by Carter and Kulhawy (1992), and Shadlou and Bhattacharya (2016) accounting for the effect of the pile diameter were compared to the FE results.
Keywords: offshore wind turbines; monopile; sand; combined; loading; numerical modelling; loading capacity; pile-soil; interaction